Kinetic Mechanism of Translocation and dNTP Binding in Individual DNA Polymerase Complexes - Lieberman, Kate R. (2013)
Complexes formed between phi29 DNA polymerase (DNAP) and DNA fluctuate discretely between the pre-translocation and post-translocation states on the millisecond time scale. The translocation fluctuations can be observed in ionic current traces when individual complexes are captured atop the α-hemolysin nanopore in an electric field. The presence of complementary 2′-deoxynucleoside triphosphate (dNTP) shifts the equilibrium across the translocation step toward the post-translocation state. Here we have determined quantitatively the kinetic relationship between the phi29 DNAP translocation step and dNTP binding. We demonstrate that dNTP binds to phi29 DNAP-DNA complexes only after the transition from the pre-translocation state to the post-translocation state; dNTP binding rectifies the translocation but it does not directly drive the translocation. Based on the measured time traces of current amplitude, we developed a method for determining the forward and reverse translocation rates, and the dNTP association and dissociation rates, individually at each dNTP concentration and each voltage. The translocation rates, and their response to force, match those determined for phi29 DNAP-DNA binary complexes and are unaffected by dNTP. The dNTP association and dissociation rates do not vary as a function of voltage, indicating that force does not distort the polymerase active site, and that dNTP binding does not directly involve a displacement in the translocation direction. This combined experimental and theoretical approach, and the results obtained, provide a framework for separately evaluating the effects of biological variables on the translocation transitions and their effects on dNTP binding.